Quality of the life of the TB patients - V. B. Zafirova; A. A. Tretyakov; K. R. Amlaev; O. V. Baronova (Кубанский научный медицинский вестник, 2015)
In the article the results of studying the quality of the life of patients with tuberculosis are represented. By the authors were interviewed 500 patients GBUz SK «Boundary antitubercular dispensary» (g. Stavropol'). Is reliably established reduction in the quality of the life of TB patients, which was manifested in a constant fatigue; the constantly decreased mood; reduction in the ability to work; worsening in the sexual life; worsening in the nourishment; reduction in the incomes; the appearance of family problems and the disintegration of family. Is established the connection between the health of patients and the form of their illness, and also other social and economic factors. Conclusion about the need for considering the obtained facts during the organization of medico-social aid to patients with tuberculosis is made.